Analisis Efektivitas Layanan Kependudukan Dengan Menggunakan Aplikasi Alpukat Betawi Di Kelurahan Johar Baru - Mila Cantika; Ivan Budi Susetyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The purpose of the study was to analyze the effectiveness of population services using the 'ALPUKAT Betawi' application in Johar Baru Urban Village, and identify obstacles and efforts to overcome them in population services process using the 'ALPUKAT Betawi' application. This research is a qualitative research with a descriptive approach, where primary data was obtained through interviews and secondary data through observation and documentation. Sources of data were several informants consisting of 2 people from service providers, 3 service recipients, and 1 academician. Based on the results of the study, it can be concluded that population services using the 'ALPUKAT Betawi' application have been running quite effectively. However, service providers need to receive more training, public understanding of the Betawi ALPUKAT application and service procedures is still low, and the internet network is not stable. To overcome these obstacles, training for providers needs to be improved, the existence of the ALPUKAT Betawi application and its service procedures need to be promoted to the public, and the internet network needs to be improved and made stable.